2020
DOI: 10.1111/aec.12935
|View full text |Cite
|
Sign up to set email alerts
|

Mistletoe litter accelerates the decomposition of recalcitrant host litter in a semi‐arid savanna, south‐west Zimbabwe

Abstract: Litter mixing plays an important role in enhancing carbon and nutrient cycling, but little is known about the effects of nutrient-rich mistletoe litter on the decomposition of slow-decaying litter in nutrient-poor environments. We investigated the effects of mistletoe litter on the decomposition and nutrient release of host Vachellia karroo litter in semi-arid savanna, southwest Zimbabwe. Mass loss and nutrient release was quantified in litter of each single species, two-species, three-species and four-species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have mainly focused on the impacts of mistletoes on their hosts and have clearly shown that mistletoes decrease host tree growth (Camarero et al ., 2019; Bilgili et al ., 2020), alter host wood and leaf anatomy (Teixeira‐Costa & Ceccantini, 2015; Ozturk et al ., 2019), and exacerbate the water deficiency of hosts (Sangüesa‐Barreda et al ., 2013; Tamudo et al ., 2021). However, mistletoes have recently been recognized as a beneficial keystone species in the ecosystem (Watson, 2009; Těšitel et al ., 2021), playing important roles in biogeochemical cycles (March & Watson, 2010; Ndagurwa et al ., 2020). Some positive influences of mistletoes include increasing the input of nutrient‐rich litter due to low nutrient resorption efficiency (Scalon et al ., 2017), affecting the temporal–spatial litterfall patterns and nutrient dynamics due to their patchy distribution (March & Watson, 2010), hastening nutrient return by accelerating the decomposition of recalcitrant host litters (Ndagurwa et al ., 2020), and increasing soil nutrient concentrations beneath infected trees (Ndagurwa et al ., 2014; Muvengwi et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mainly focused on the impacts of mistletoes on their hosts and have clearly shown that mistletoes decrease host tree growth (Camarero et al ., 2019; Bilgili et al ., 2020), alter host wood and leaf anatomy (Teixeira‐Costa & Ceccantini, 2015; Ozturk et al ., 2019), and exacerbate the water deficiency of hosts (Sangüesa‐Barreda et al ., 2013; Tamudo et al ., 2021). However, mistletoes have recently been recognized as a beneficial keystone species in the ecosystem (Watson, 2009; Těšitel et al ., 2021), playing important roles in biogeochemical cycles (March & Watson, 2010; Ndagurwa et al ., 2020). Some positive influences of mistletoes include increasing the input of nutrient‐rich litter due to low nutrient resorption efficiency (Scalon et al ., 2017), affecting the temporal–spatial litterfall patterns and nutrient dynamics due to their patchy distribution (March & Watson, 2010), hastening nutrient return by accelerating the decomposition of recalcitrant host litters (Ndagurwa et al ., 2020), and increasing soil nutrient concentrations beneath infected trees (Ndagurwa et al ., 2014; Muvengwi et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, community-level impacts of mistletoes are seen beyond their hosts through the production of nutrient-rich litter that enhances host litter decomposition and contributes to carbon and nutrient fluxes in ecosystems (Ndagurwa et al, 2020), as well as attraction of seed dispersers that bring in and deposit (as excreta) the seeds of other plants, promoting increased plant diversity in forests (Těšitel et al, 2021). These effects, when combined, facilitate changes in the composition of soil microbiota, vegetation, and associated herbivore fauna beneath parasitized trees, leading to long-term vegetation shifts and habitat restructuring (Hódar et al, 2018;Mellado & Zamora, 2017;Ndagurwa et al, 2014;Watson & Herring, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mistletoes can therefore exert an ambivalent effect on host plants by facilitating their reproduction through the attraction and permanent support of shared generalist pollinators and vectors (Těšitel et al, 2021), but at the same time reducing the physiological fitness of the hosts by depletion of their water and nutrient supplies and increasing susceptibility to pathogens and herbivores (Griebel et al, 2017). Furthermore, community‐level impacts of mistletoes are seen beyond their hosts through the production of nutrient‐rich litter that enhances host litter decomposition and contributes to carbon and nutrient fluxes in ecosystems (Ndagurwa et al, 2020), as well as attraction of seed dispersers that bring in and deposit (as excreta) the seeds of other plants, promoting increased plant diversity in forests (Těšitel et al, 2021). These effects, when combined, facilitate changes in the composition of soil microbiota, vegetation, and associated herbivore fauna beneath parasitized trees, leading to long‐term vegetation shifts and habitat restructuring (Hódar et al, 2018; Mellado et al, 2016; Mellado & Zamora, 2017; Ndagurwa et al, 2014; Watson & Herring, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, very few studies address litter diversity effects on decomposition in these ecosystems (e.g. Ndagurwa et al, 2020). This lack of data across ecosystems impedes an assessment of the effects of environmental parameters and their interaction with litter traits on litter mixture effects (Porre et al, 2020).…”
Section: Introductionmentioning
confidence: 99%